Multimodal brain connectivity analysis in unmedicated late-life depression. - Reza Tadayonnejad; Shaolin Yang; Anand Kumar; Olusola Ajilore (PLoS ONE)
Late-life depression (LLD) is a common disorder associated with emotional distress, cognitive impairment and somatic complains. Structural abnormalities have been suggested as one of the main neurobiological correlates in LLD. However the relationship between these structural abnormalities and altered functional brain networks in LLD remains poorly understood. 15 healthy elderly comparison subjects from the community and 10 unmedicated and symptomatic subjects with geriatric depression were selected for this study. For each subject, 87 regions of interest (ROI) were generated from whole brain anatomical parcellation of resting state fMRI data. Whole-brain ROI-wise correlations were calculated and compared between groups. Group differences were assessed using an analysis of covariance after controlling for age, sex and education with multiple comparison correction using the false discovery rate. Structural connectivity was assessed by tract-based spatial statistics (TBSS). LLD subjects had significantly decreased connectivity between the right accumbens area (rA) and the right medial orbitofrontal cortex (rmOFC) as well as between the right rostral anterior cingulate cortex (rrACC) and bilateral superior frontal gyrus (bsSFG). Altered connectivity of rrACC with the bsSFG was significantly correlated with depression severity in depressed subjects. TBSS analysis showed a 20% reduction in fractional anisotropy (FA) in the right Forceps Minor (rFM) in depressed subjects. rFM FA values were positively correlated with rA-rmOFC and rrACC-bsFG functional connectivity values in our total study sample. Coordinated structural and functional impairment in circuits involved in emotion regulation and reward pathways play an important role in the pathophysiology of LLD.